Additive nanomanufacturing - A review - Engstrom, D; Porter, B; Pacios, M; Bhaskaran, H (2014)
Additive manufacturing has provided a pathway for inexpensive and flexible manufacturing of specialized components and one-off parts. At the nanoscale, such techniques are less ubiquitous. Manufacturing at the nanoscale is dominated by lithography tools that are too expensive for small- and medium-sized enterprises (SMEs) to invest in. Additive nanomanufacturing (ANM) empowers smaller facilities to design, create, and manufacture on their own while providing a wider material selection and flexible design. This is especially important as nanomanufacturing thus far is largely constrained to 2-dimensional patterning techniques and being able to manufacture in 3-dimensions could open up new concepts. In this review, we outline the state-of-the-art within ANM technologies such as electrohydrodynamic jet printing, dip-pen lithography, direct laser writing, and several single particle placement methods such as optical tweezers and electrokinetic nanomanipulation. The ANM technologies are compared in terms of deposition speed, resolution, and material selection and finally the future prospects of ANM are discussed. This review is up-to-date until April 2014. Copyright © Materials Research Society 2014.